Antigone’s Claim. Norm and Non-Normative Model of the Family by Judith Butler - Lubowicka, Grażyna (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2022)
Judith Butler’s problems in Antigone’s Claim concern a decomposed and diverse family in postmodernity or a family subjected to deformations and displacements, and the question about which model(s) the family may be heading. The traditional family model based on the primacy of the heterosexual matrix of family and sexuality is deconstructed by Butler by unmasking the basic prohibition of homosexuality for culture and based on the assumption that interpersonal bonds aregenerated in a historical social space. Butler proposes a new relationship ontology in which human lust is not governed by the imperative of heterosexuality.
Keywords: Antigone; family; performativity; cultural norm